The Effectiveness of The Learning by Doing Method in Teaching Speaking to 7th Grade Students at SMPN 14 Mataram - Zahara, Baiq Ane Balqis; Thohir, Lalu; Junaidi, Ahmad; Arifuddin, Arifuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The purpose of this study was to investigate whether the implementation of the Learning by Doing method is effective in improving students' speaking ability at SMPN 14 Mataram. This study used a quantitative approach with a pre-experimental design with involving 31 students at SMPN 14 Mataram. The data were collected by using pre and post-test on students' speaking performance in terms of fluency, pronunciation, grammar, vocabulary, and comprehension. Data were analyzed by using SPSS with a paired sample t-test. The findings of the study reveal that there was a significant difference between the scores before and after treatment. In which the average score of students in the pre-test was 54.58 and became 79.29 in the post-test and the results of the hypothesis testing of this study (2-tailed) is 0.00 (<0.05). Therefore, it can be concluded that the implementation of the Learning by Doing method has a significant positive effect on students' speaking skill.